2012
DOI: 10.1111/j.1432-2277.2012.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes with respect to disabilities of the upper limb after hand allograft transplantation: a systematic review

Abstract: Summary The aim of this work is to compare disabilities of the upper limb before and after hand allograft transplantation (HAT), and to describe the side effects of immunosuppressive (IS) agents given to recipients of hand allografts. Clinical cases of HAT published between 1999 and 2011 in English, French, or German were reviewed systematically, with emphasis on comparing disabilities of the arm, shoulder and hand (DASH) scores before and after transplantation. Duration of ischemia, extent of amputation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 57 publications
0
58
0
Order By: Relevance
“…For each case a precise plan and in some cases development of novel reconstruction techniques are required Landin et al 2012). At present, definite recommendations regarding the maximum duration of ischemia do not exist; however, ischemia time should be kept as short as possible and not exceed 10 hours.…”
Section: Preparation and Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…For each case a precise plan and in some cases development of novel reconstruction techniques are required Landin et al 2012). At present, definite recommendations regarding the maximum duration of ischemia do not exist; however, ischemia time should be kept as short as possible and not exceed 10 hours.…”
Section: Preparation and Surgical Proceduresmentioning
confidence: 99%
“…As mentioned above, the functional outcome after transplantation at more proximal levels requires prolonged rehabilitation and is overall less consistent (Landin et al 2012). The functional return in these cases may continue to improve during the first 5 years after trans-…”
Section: Motor Functionmentioning
confidence: 99%
“…Sensory and motor recovery in hand transplant recipients has conferred the ability to perform daily activities, including eating, driving, grasping objects, shaving, using the telephone and writing [3 •• ]. Landin et al described improved function following hand transplantation, as reported by patients themselves, using the disabilities of arm, shoulder and hand questionnaire [37]. As with facial transplantation, ongoing motor improvements in hand transplant recipients, including ability to perform fine tasks such as pick up ballbearings, have been observed more than 5 years after transplantation [3 •• , 42].…”
Section: Functional Outcomesmentioning
confidence: 99%
“…1 There has been variable return of motor and sensory function following VCA, which is ultimately dependent on the success of nerve regeneration. [2][3][4] Strategies to improve peripheral nerve regeneration are paramount to this field. This review discusses the current knowledge and practices in the field of peripheral nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%